Worsening renal function as an outcome predictor in patients with new onset atrial fibrillation on direct oral anticoagulant. (14th October 2021) - Bartoli, L; Angeli, F; Stefanizzi, A; Armillotta, M; Sansonetti, A; Magnani, I; Fabrizio, M; Paolisso, P; Foa', A; Rinaldi, A; Galie', N; Pizzi, C
Abstract: Background: In patients with atrial fibrillation (AF), baseline kidney function is used to guide oral anticoagulant (OA) selection and dosing, and chronic kidney disease (CKD) is a significant outcome predictor. However, the incidence of worsening renal function (WRF) and its prognostic role during treatment with direct oral anticoagulants (DOACS) has been poorly explored. Purpose: To assess the prognostic role of WRF in terms of bleedings and major adverse cardiovascular events (MACEs) in a cohort of patients with newly diagnosed non-valvular AF (NVAF) treated with DOACs. Methods: Between January 2017 and March 2019, we enrolled all the patients with newly diagnosed NVAF and OA indication, treated with DOACs. Renal function was assessed using the mean value of the estimated glomerular filtration rates (eGFR) calculated using Cockcroft-Gault (CG), Modification of Diet in Renal Disease (MDRD) and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formulas. CHA2DS2-VASc and HAS-BLED scores were used at baseline to estimate the ischemic and hemorrhagic risk, respectively. At follow-up, WRF was identified as a decrease in eGFR of at least 20% while bleedings were classified according to the international society of thrombosis and hemostasis (ISTH) criteria. Finally, we defined AF progression as the transition from paroxysmal to persistent or permanent AF or from persistent to permanent AF. Results: 1009 patients with newly diagnosed NVAF started on DOAC were enrolled. They were followed-up for 21.6±9.5 months. Overall, WRF was observed in 181 cases (18%). Patients with WRF had higher rates of progression of atrial fibrillation (18.5% vs 11.8%, p=0.02), MACEs (20.4% vs 12.9%, p=0.09) and major bleedings (MB) (9, 4% vs 4, 7%, p=0.013). WRF did not correlate with all bleedings, stroke, or acute coronary syndrome (ACS). However, those who presented WRF using CKD-EPI formula had higher ACS incidence (6.1% vs 2.5%, p=0.015), and generally better-predicted MACEs. At multivariate analysis adjusted for age, hypertension, baseline HAS-BLED score and WRF, the latter emerged as an independent predictor of MB (OR 1.9 95% C.I, 1, 059–3, 51). Conclusion: In patients with newly diagnosed NVAF treated with DOACs, WRF is associated with atrial fibrillation progression and MACEs, and emerged as an independent predictor of major bleedings. WRF evaluated with CKD-EPI formula better predicted MACEs. Funding Acknowledgement: Type of funding sources: None.